2010
DOI: 10.1103/physrevlett.104.166402
|View full text |Cite
|
Sign up to set email alerts
|

Pinning and Depinning of the Polarization of Exciton-Polariton Condensates at Room Temperature

Abstract: A room temperature polariton condensate realized in a microcavity with embedded GaN quantum wells emits linearly polarized light at threshold with the plane of polarization pinned to one of the crystallographic axes. With increasing pumping power, a depinning of the polarization is observed resulting in a progressive decrease of the polarization degree of the emitted light. This depinning is understood in terms of polariton-polariton repulsion competing with the static disorder potential effect. The polarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
45
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 23 publications
8
45
1
Order By: Relevance
“…3,4,7,11 . The dynamical equations for the condensate wavefunctions corresponding to the left ψ − and right ψ + hand circular polarization states are written as follows (σ = ±) 8 :…”
Section: The Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…3,4,7,11 . The dynamical equations for the condensate wavefunctions corresponding to the left ψ − and right ψ + hand circular polarization states are written as follows (σ = ±) 8 :…”
Section: The Modelmentioning
confidence: 99%
“…It is usually assumed that all memory of the polarization of the incoherent pump is lost 3,11 . However, as mentioned above, it was shown that the creation of a spin-polarized exciton reservoir is possible with a spin-imprinting optical pump for sufficiently short-lived excitons.…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Stimulated scattering of exciton polaritons into the lowest energy state leads to so-called polariton lasing, recently observed in GaAs, CdTe, and GaN based microcavities. 13,14 If the scattering from the upper to the lower polariton branch was accompanied by the emission of terahertz photons, polariton lasers would emit terahertz radiation, and this emission would be stimulated by the population of the lowest energy polariton state. However, at first glance, this process is forbidden since an optical dipole operator cannot directly couple the polariton states formed by the same exciton state.…”
mentioning
confidence: 99%